Prevalence of refractive errors and color vision deficiency in a population of industry-workers in Abhar, Iran. Issue 46 (19th November 2021) - Ahadi, Masoumeh; Ebrahimi, Afsaneh; Rahmani, Saeed; Baghban, Alireza Akbarzadeh
Abstract : Abstract: Visual impairment due to refractive errors and color vision deficiency (CVD) can affect the visual abilities of workers in workplace. Identifying the prevalence of common visual problems helps us to prevent and treat occupational ocular problems. This study was conducted on 2600 males referring from companies for a routine medical exam to Occupational Medicine Center. In all subjects, visual acuity and refraction were measured. Assessment of color vision was performed by Ishihara color test. In present study, right eyes of subjects were selected to statistical analysis. The mean spherical equivalent was –0.19 ± 1.39 diopter with a range of –11.00 to +10.00 diopter. Whereas 71% of persons were emmetropic, 20% and 9% of them were myopic and hypermetropic, respectively. From a total subjects, 164 of them had CVD with prevalence of color blindness of 6.3%. In comparison with normal subjects, CVD had no significant effect on refractive findings of our subjects ( P > .05). Our data present the prevalence of refractive errors and color blindness among Iranian industry-workers. Compared with other studies, our subjects have a lower prevalence of refractive errors, and similar rate of prevalence of color blindness.